2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8462521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Aperture Design in Computational Imaging

Abstract: There is growing interest in the use of coded aperture imaging systems for a variety of applications. Using an analysis framework based on mutual information, we examine the fundamental limits of such systems-and the associated optimum aperture coding-under simple but meaningful propagation and sensor models. Among other results, we show that when thermal noise dominates, spectrally-flat masks, which have 50% transmissivity, are optimal, but that when shot noise dominates, randomly generated masks with lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Among other things, the analysis showed that when shot noise dominates thermal noise, randomly generated masks with lower transmissivity than 1/2 offered greater performance compared to spectrally flat patterns of transmissivity 1/2. This paper extends the work of [14] in multiple respects that may be broadly grouped into the following three main contributions.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Among other things, the analysis showed that when shot noise dominates thermal noise, randomly generated masks with lower transmissivity than 1/2 offered greater performance compared to spectrally flat patterns of transmissivity 1/2. This paper extends the work of [14] in multiple respects that may be broadly grouped into the following three main contributions.…”
Section: Introductionmentioning
confidence: 81%
“…Another issue is obtaining a good understanding of mask/lens combinations. This will require not only updates to the simple propagation model studied here and in [14], but also a refined understanding of the cost tradeoffs between lenses and apertures.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The computation in (14) takes 2M 2 + 2M multiplications. We then feed our gradients to minfunc solver [33] with L-BFGS algorithm [34] to solve the non-linear optimization problem in (7).…”
Section: Algorithm Analysismentioning
confidence: 99%